Ash Whitefly, Siphoninus phillyreae (Haliday) (Insecta: Homoptera: Aleyrodidae: Aleyrodinae) - Ru Nguyen; Avas B. Hamon (EDIS)
Ash whitefly, Siphoninus phillyreae, was described as Aleyrodes phillyreae by Haliday (1835), on Phillyrea latifolia collected in Dublin, Ireland. It has several synonyms listed in Mound and Halsey (1978). In the United States, S. phillyreae was first collected in Los Angeles County, California in 1988, and has since spread to Kern, Orange, Riverside, Sacramento, San Bernardino, San Diego, Santa Barbara, Santa Clara, Stanislaus, Tulare and Ventura counties. Most ash whiteflies in California were found on pomegranate, ash tree, pear, apple, loquat and citrus. It causes severe damage to pear and apple in Europe. Heavy infestations caused leaf wilt, early leaf drop and smaller fruit (Bellows et al. 1990). If this whitefly is introduced into Florida we expect it to become a pest of ornamental plants and possibly other crops. This document is EENY-147, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: August 2000. Revised: November 2002.